"At least David Cameron resigned": The protective effects of just-world beliefs for counterfactual thinking after Brexit. (15th January 2018) - Sirois, Fuschia M.; Iyer, Aarti
Abstract: Following an unexpected geo-political event, such as the United Kingdom's June 2016 referendum vote to leave the European Union ("Brexit"), people will make counterfactuals that mentally undo the outcome and imagine what might have been had the outcome gone in the predicted direction. Yet little is known about how such counterfactuals may impact well-being, or the individual differences that might protect individuals from making potentially distressing upward counterfactuals. We examined the extent to which individual differences in enduring just-world beliefs shape the number of upward counterfactuals generated by British "Remain" voters, and the resulting effects on vote-related well-being. Participants who were directed to make counterfactuals reported the same levels of vote-related well-being as those who were not directed to make counterfactuals. Among those who made counterfactuals, making more upward counterfactuals was associated with reduced well-being. However, holding just-world beliefs limited the number of upward counterfactuals that were made and thus protected individuals from this distress. Our findings demonstrate that individual differences in enduring beliefs about the fairness of a vote may protect voter well-being when there will not be a second vote. Highlights: The role of just-world beliefs in making counterfactuals after Brexit was tested. Making more upward counterfactuals was linked to lower well-being. Other just-world beliefs limited upward counterfactuals and reduced distress. Just-world beliefs are protective from distress after a negative vote outcome.